Natural Scientific Thinking in Foreign Students of Pre-University Courses in the Context of Integration into the Russian Educational Environment - Fisenko, O.; Nikitina, V.; Satina, T. (Jurnal Pendidikan IPA Indonesia, 2021)
This article is the result of a two-year-long experiment conducted by the authors. The purpose of the research was to study the natural scientific thinking of foreign students of preparatory departments in the context of integrative processes. The quantitative and qualitative analysis of the regulatory framework governing the educational process at the stage of pre-university training, including syllabi and steering documents of faculties of pre-university training, formed the methodological basis of the research. The modified criteria-focused TEM-11 test was used as a diagnostic tool. The method of expert evaluations ensured the reliability and validity of the research. The study provided evidence of the feasibility of including an integration course in “biophysics” along with biology, physics, and chemistry in the curricula of preparatory departments that prepare foreign students for admission to medical, agricultural, veterinary, and biological faculties. It does not appear reasonable to include an online course in the training system for foreign students who are residents since they already developed the differential-synthetic and synthetic stages of natural scientific thinking while they were learning the trade. It is concluded that the Biophysics integrative online course studied by foreign students of faculties of pre-university training, develops a special type of natural scientific thinking, which will be the basis for framing professional thinking in the future. A total of 374 people took part in the experiment (188 people were included in the experimental group and 186 people became part of the control group). The comparative analysis of the stages of development of natural scientific thinking in the control and experimental groups showed significant progress in the experimental group. After the experiment, the number of respondents at the common empirical stage of development of natural scientific thinking was 11.2 % of the entire sample; the number of respondents at the scientific empirical stage was 32.8 %, at the synthetic differential stage – 44.7 % and at the synthetic stage – 27.6 %.